Memahami Perang Siber dan Peran Badan Intelijen Negara Dalam Menangkal Ancaman di Siber - M. Yusuf Samad; Pratama Dahlian Persadha (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2022)
Cyber attacks that target a country have occurred in Georgia, Estonia and Ukraine, these attacks were able to paralyze vital infrastructure in both countries. Similar attacks have the potential to occur in Indonesia, so it is necessary to understand the mechanism of cyber attacks and how to prevent them. This study uses a qualitative approach with the aim of understanding cyber attacks through the Russian cyber war against Estonia and Georgia. In addition, this study also aims to understand the role of the State Intelligence Agency in countering cyber threats in Indonesia. The findings of this study are cyber attacks against Giorgia and Estonia through each stage of Cyber Early Warning. In preventing similar attacks, BIN plays a role in preventing cyber attacks by coordinating intelligence, cyber patrols and security assessments